2019
DOI: 10.12688/wellcomeopenres.15136.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dried blood spots for DNA methylation profiling

Abstract: Background: DNA methylation reflects health-related environmental exposures and genetic risk, providing insights into aetiological mechanisms and potentially predicting disease onset, progression and treatment response. An increasingly recognised need for large-scale, longitudinally-profiled samples collected world-wide has made the development of efficient and straightforward sample collection and storage procedures a pressing issue. An alternative to the low-temperature storage of EDTA tubes of venous blood … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…Finally, our measures of EAA were derived from DBS samples, rather than whole blood collection, which is the more widely used approach, particularly in research done in laboratory and clinical settings, as opposed to at field sites such as ours. However, recent research found that matched DBS and EDTA tube samples were highly correlated for DNA methylation (r = 0.99), so we are confident that our results reflect those measured in blood (Walker et al, 2019).…”
Section: M Itati O N Ssupporting
confidence: 67%
“…Finally, our measures of EAA were derived from DBS samples, rather than whole blood collection, which is the more widely used approach, particularly in research done in laboratory and clinical settings, as opposed to at field sites such as ours. However, recent research found that matched DBS and EDTA tube samples were highly correlated for DNA methylation (r = 0.99), so we are confident that our results reflect those measured in blood (Walker et al, 2019).…”
Section: M Itati O N Ssupporting
confidence: 67%
“…Quality control (QC) and normalisation were conducted using R packages ‘ShinyMethyl’ (version 1.28.0) [ 34 ], ‘watermelon’ (version 1.36.0) [ 35 ] and ‘meffil’ (version 1.1.1) [ 36 ]. Details of the protocol are described elsewhere [ 37 ]. In summary, quality control procedures removed probes if there was an outlying log median methylated signal intensity against unmethylated signal for each array, or a bead count <3 in ≥5 % of the total probe sample, or a detection p -value >0.05 for set 1 and p -value >0.01 for set 2 in ≥0.5% of the total sample in each respective set.…”
Section: Methodsmentioning
confidence: 99%
“…Self-reported smoking status, smoking pack years, DNAm-estimated white-blood cell proportions (CD8+T, CD4+T, natural killer cells, B cells and granulocytes) [ 37 ], batch, the first 20 principal component derived from the M -values, the first 10 principal components derived from the imputed genetic data, age and sex were included as covariates for the discovery methylome-wide association analysis (see Additional file 1 : Supplementary Methods and Additional file 1 : Table S3 for details). Where possible, the same covariates were used in the replication analyses, although only smoking status (and not pack years) was available in LBC 1921, LBC 1936 and ALSPAC.…”
Section: Methodsmentioning
confidence: 99%
“…We used the DBS technique, which is a relatively new sampling method in the context of methylation analyses. The latest publications are promising and suggest that this handy and simple technique is reliable and valid in the assessment of methylation marks (reviewed in 54, 63). As mentioned above, cell composition can be a potential confounder, which was not controlled for in the present analyses and therefore needs to be considered as a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosine methylation was assessed from dried blood spot (DBS) DNA samples, as previously described elsewhere (see, e.g., 61, 62, 63). The Qiagen QIAamp DNA Investigator Kit (Qiagen, Hombrechtikon, Switzerland) was used to extract genomic DNA from three punches of blood-soaked filter paper (each 3 mm in diameter).…”
Section: Methodsmentioning
confidence: 99%